2021
DOI: 10.3390/molecules26144382
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Organic Liquid Products Deoxygenation by Multistage Countercurrent Absorber/Stripping Using CO2 as Solvent with Aspen-HYSYS: Thermodynamic Data Basis and EOS Modeling

Abstract: In this work, the thermodynamic data basis and equation of state (EOS) modeling necessary to simulate the fractionation of organic liquid products (OLP), a liquid reaction product obtained by thermal catalytic cracking of palm oil at 450 °C, 1.0 atmosphere, with 10% (wt.) Na2CO3 as catalyst, in multistage countercurrent absorber/stripping columns using supercritical carbon dioxide (SC-CO2) as solvent, with Aspen-HYSYS was systematically investigated. The chemical composition of OLP was used to predict the dens… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…hydrocarbons and 10% (area.) oxygenates, and that acidity is mainly due to the presence of carboxylic acids, OLP has been described by the key-compounds hydrocarbons (Decane, Undecane, Tetradecane, Pentadecane, Hexadecane, and Octadecane) and oxygenates (Palmitic acid, Oleic acid) [112][113]. The simulations performed by selecting the unit operation multistage countercurrent absorber, as the dissolution/solubilization of gases (CO2) in liquids (OLP) is a function of state conditions (P, T), and that a fraction of the coexisting liquid phase dissolves in the gas phase, like a gas (CO2)-liquid (OLP) equilibrium behavior.…”
Section: Simulation Methodologymentioning
confidence: 99%
See 3 more Smart Citations
“…hydrocarbons and 10% (area.) oxygenates, and that acidity is mainly due to the presence of carboxylic acids, OLP has been described by the key-compounds hydrocarbons (Decane, Undecane, Tetradecane, Pentadecane, Hexadecane, and Octadecane) and oxygenates (Palmitic acid, Oleic acid) [112][113]. The simulations performed by selecting the unit operation multistage countercurrent absorber, as the dissolution/solubilization of gases (CO2) in liquids (OLP) is a function of state conditions (P, T), and that a fraction of the coexisting liquid phase dissolves in the gas phase, like a gas (CO2)-liquid (OLP) equilibrium behavior.…”
Section: Simulation Methodologymentioning
confidence: 99%
“…The OLP deoxygenation process, using SC-CO2 as solvent, was simulated using Aspen- HYSYS 8.6 (Aspen One, 2015). The simulations performed by selecting the multistage countercurrent absorber/stripping unit operation because of its similarities and/or theoretical thermodynamic fundamentals of solubility of gas in liquids, as the phase equilibrium behaves like a gas-liquid coexisting phases, as described elsewhere [112][113]. Aspen-HYSYS 8.6 computes the countercurrent multistage absorber column unit operations by applying the inside-out algorithm to solve simultaneously materials and energies balances stage-to-stage coupled with a rigorous thermodynamic model.…”
Section: Simulation Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…hydrocarbons and 10% (area.) oxygenates, and found that acidity is mainly due to the presence of carboxylic acids, whereby OLP has been described by the key compounds of hydrocarbons ( decane , undecane , tetradecane , pentadecane , hexadecane , and octadecane ) and oxygenates ( palmitic acid , oleic acid ) [ 59 , 60 ]. The simulations were performed by selecting the unit operation multistage countercurrent absorber, as the dissolution/solubilization of gases (CO 2 ) in liquids (OLP) is a function of state conditions (P, T), whereby a fraction of the coexisting liquid phase dissolves in the gas phase, such as with a gas (CO 2 )–liquid (OLP) equilibrium behavior.…”
Section: Methodsmentioning
confidence: 99%